Kontribusi Pemikiran Ekonomi Syari'Ah di Abad Ke 5-11 M dalam Aktivitas Perekonomian di Indonesia - Zikwan, M. (Proceedings of Annual Conference for Muslim Scholars, 2019)
The rise of Shari'ah economic discussion is something that has to happen especially for a country with a more Muslim population than a Muslim minority country. this happens because the shari'ah economy has given the biggest contribution to the improvement and economic growth of the Ummah. However, talking about sharia economics is inseparable from the history in which the shariah economy was built. History has incised its ink, that contemporary sharia economic thought is inseparable from the contribution of the thoughts of Muslim scholars in the 5th to the 11th centuries AD. This phase is known as establishing the foundations of Islamic economics, which was initiated by the jurists accompanied by Sufi figures as well as philosophers. Economic thinking based on fiqh discusses economic phenomenon by exploring the concepts of maslahah and Mafsa. Part of this thought contribution has been adopted and applied in the Republic of Indonesia today. such as the construction of zakat management bodies, supervision of product sales and so on. The application of Islamic economics is often present in the form of financial institutions such as the development of Islamic financial institutions in the form of banking or the like. The minds of scholars in the past have contributed to modern economists today, where most Muslim-majority countries prefer sharia economics as their country's economic system